Contribuciones of the holy see to the disarmament. Commitment to peace (Pontifical Comisión Iustitia Et Pax, Vatican City, 1984)
Education for peace is one of the major eiements in any commitment to building a world where the ideals of peace predominate over the temptation to war and violence. Recently, His Eminence AgostinoCardinal Casaroli, Secretary of State to Pope John Paul II, was invited to accept a doctorate honoris causa from the Jesuit run University of San Francisco in California. The Cardinal used that occasion to deliverdiscourse on the challenge of peace today. Given to the faculty and students of the University on 18 November 1983, the speech is meant to be a commentary on the Message which John Paul II had sent to the Second Special Session on Disarmament of the United Nations General Assembly, 11 June 1982. The Cardinal’s thoughts were not meant to be an official interpretation of the Pope’s Message. Rather, they are a commentary on the various points raised by the Pontiff with the aim of offering a further reflection on these crucial questions. It is then a presentation of the ideas and insights of the person who has worked most closely with the current Pope and with his predecessor, Paui VI, in the international field